Infamous people between crime and sin: the new feuilletonists and their moralist portrayals of the underworld: Los neofolletinistas y sus representaciones moralistas de los bajos fondos - Vergara Aguirre, Andrés (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
José Antonio Osorio Lizarazo and Ximénez were two acknowledged new feuilletonists of Bogatan press between the 1920s and 1940s. Their sketches show the deep scar of their years in catholic schools, something that becomes evident in their portrayals of the city's underworld, where they tend to mix up crime and sin in dichotomic manichean relations: good and bad, God and Devil, heaven and hell, saints and sinners. We propose a hermeneutical reading of such portrayals in relation to the reporters' religious background.